Association between maternal adversity, DNA methylation, and cardiovascular health of offspring: a longitudinal analysis of the ALSPAC cohort study. Issue 3 (24th March 2022) - Hyde, Natalie K; Dowty, James G; Scovelle, Anna; Armstrong, Gregory; Sutherland, Georgina; Olive, Lisa; Lycett, Kate; O'Neil, Adrienne
Abstract : Objectives: Maternal adversity during pregnancy has been shown to be associated with some health outcomes in the offspring. This study investigated the association of maternal adversity during pregnancy and DNA methylation with offspring cardiovascular (CV) health. Design: Longitudinal observational cohort study Setting: All pregnant residents in county Avon (∼0.9 million), UK, were eligible to participate if their estimated delivery date was between 1 April 1991 and 31 December 1992. Participants: Mother–offspring pairs enrolled in the Avon Longitudinal Study of Parents and Children cohort at seven (n=7431) and 17 years of age (n=3143). Primary and secondary outcome measures: Offspring CV health primary measures were heart rate (HR), blood pressure (BP) and secondary measures were pulse-wave velocity and carotid intima–media thickness. Results: Overall, there was no association between maternal adversity scores (number or perceived impact) and primary CV measures (Perceived impact; HR: 0.999-fold change 95% CI 0.998 to 1.001; systolic BP (SBP): 1.000-fold change 95% CI 0.999 to 1.001; diastolic BP: 1.000-fold change 95% CI 0.999 to 1.002). Some small offspring sex effects were observed and there was also a small association between methylation of some CpG sites and offspring BP measures. Conclusions: We found little evidence to support the overall association of maternal adversity during pregnancy and DNA methylation with offspring CV measures. Offspring sex-specific and age-specific associations require further investigation.